Making university-of-the-future relevance in the digital age: community engagement in enhancing the wellbeing of B40 LIbyan young women through balanced digital entrepreneurship education and digital platform - Mostafa Alsharif, Rahma; Ahmad Dahlan, Abdul Rahman (Research Publish Journals, 2020)
Acquiring an education is an integral part of the Islamic faith. In fact, the first verse revealed to the Mohamed (Pbuh) was; "Read! In the Name of your Lord, who has created (all that exists), Has created man from a clot (a piece of thick coagulated blood). Read! And your Lord is the Most Generous" (al- ‘Alaq 96:1-3). Also, the prophet said, hadith clearly state the essentiality of education and knowledge acquisition to the Muslims. Also, in Islam, humankind is seen as Allah's vicegerent on earth. Subsequently, without proper education, Muslims would not be able to fulfil their mission as Allah's vicegerent. Being Allah's vicegerent means "being concerned with the wellbeing of other humans" (Kazmi, p.14). In other, creating a more humane world and just; where protecting people's rights and dignity is a priority (SDG16). Executing this mission requires effectively deep knowledge of Allah (S.W), understand the nature of the world we inhabit and deep understanding of the mission at hand. And this is where holistic and quality education place role. This paper offers a validated conceptual Malaysian UotF business model with a focus on international community engagement programmes. The value proposition of the conceptual business model is to enhance the wellbeing of B40 young women in Libya through humanizing digital entrepreneurship education activities and harnessing on digital capability. The design and system thinking approach has been adopted in this paper to address the wellbeing issues of the Libyan B40 young women through understanding their need, and then followed by building conceptual business models using modelling tools, i.e. Business model canvas (BMC) and Value proposition design canvas (VPC). The approach includes conducting a literature review and interviews for understanding the needs, challenges and key problems; formulating and ideating initial business model options in solving the problems; and validation of the initial business model by interviewing the various customer segments. The objective is to enhance the wellbeing of B40 young women with decent jobs and stimulate economic growth through a humanizing digital entrepreneurship programme.